2007
DOI: 10.1002/jcp.20995
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and modulation of LH/CG—receptor during human trophoblast differentiation

Abstract: 14 Moreover, on stimulation by recombinant hCG, the syncytiotrophoblast produced less cyclic AMP 15 than cytotrophoblasts, indicating that LH/CG-R expression is regulated during human villous 16 trophoblast differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 58 publications
2
55
0
4
Order By: Relevance
“…The antibodies were polyclonal goat anti-BMPR1B (sc-5679), goat anti-FSHR (sc-7798), and goat anti-LHR (sc-26341) (all from Santa Cruz Biotechnology), anti-goat second antibody conjugated with Alexa 488 (Al-Samerria & Almahbobi 2014). In addition, the antibodies have been previously reported in human studies (Haÿ et al 2004, Cai et al 2007, Pidoux et al 2007, Abir et al 2008) and using flow cytometry . Immunolocalization of LHR in human placental trophoblasts demonstrated positive strong staining with human chorionic gonadotropin, and no staining was observed in nonspecific isotypic negative controls (Pidoux et al 2007).…”
Section: Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibodies were polyclonal goat anti-BMPR1B (sc-5679), goat anti-FSHR (sc-7798), and goat anti-LHR (sc-26341) (all from Santa Cruz Biotechnology), anti-goat second antibody conjugated with Alexa 488 (Al-Samerria & Almahbobi 2014). In addition, the antibodies have been previously reported in human studies (Haÿ et al 2004, Cai et al 2007, Pidoux et al 2007, Abir et al 2008) and using flow cytometry . Immunolocalization of LHR in human placental trophoblasts demonstrated positive strong staining with human chorionic gonadotropin, and no staining was observed in nonspecific isotypic negative controls (Pidoux et al 2007).…”
Section: Receptorsmentioning
confidence: 99%
“…In addition, the antibodies have been previously reported in human studies (Haÿ et al 2004, Cai et al 2007, Pidoux et al 2007, Abir et al 2008) and using flow cytometry . Immunolocalization of LHR in human placental trophoblasts demonstrated positive strong staining with human chorionic gonadotropin, and no staining was observed in nonspecific isotypic negative controls (Pidoux et al 2007). In the same study, RT-PCR products were sequenced and confirmed LHR fragments (Pidoux et al 2007).…”
Section: Receptorsmentioning
confidence: 99%
“…The decrease in the number of sperm in the present study may be due to low level of hormone testosterone, [36] who explained that maintenance of testosterone levels very important in the process spermatogenesis and fertility. The damaged Sertoli cells in present study caused decrease in the number of sperm, As [37] indicated the toxic substances have a direct effect on the function of theSertoli cells and they are involved in controlling the spermiation, and when disturbed caused epithelial disorganization and following tubular atrophy.…”
Section: Discussionmentioning
confidence: 53%
“…Trophoblasts secrete an array of hormones (Cemerikic et al 1994;DiPirro and Kristal 2004;Gallego et al 2009Gallego et al , 2010Pidoux et al 2007;Zhuang and Li 1991) including P 4 , endorphins, hCG, 17 -estradiol (E 2 ) and gonadotropin-releasing hormone (GnRH) (Fig. 2).…”
Section: Trophoblastic Hormone Secretion During Early Embryogenesismentioning
confidence: 99%
“…2). The dramatic elevation in the production of hCG by the trophoblastic layer of the blastocyst during the early embryonic stage (from 5 to ≥1000 mIU/mL in the maternal serum; Braunstein 1976; Pidoux et al 2007) signals both the corpus lutea and trophoblast (Golos, et al 2006) to synthesize and secrete P 4 (Bukovsky et al 1995;Carr et al 1982;Casper and Yen 1979;Duncan et al 1996;Richardson and Masson 1985;Strauss et al 2000). Trophoblastic secretion of these hormones appears to occur during the migration of the blastocyst through the fallopian tube and its implantation into the endometrium and subsequently from the placental tissues during later stages of embryogenesis.…”
Section: Trophoblastic Hormone Secretion During Early Embryogenesismentioning
confidence: 99%